30-day morbidity and mortality after hip surgery – A single-centre study. - Junaid Khan; Usman Ali; Muhammad Zohaib Nawaz; Muhammad Talal Ibrahim; Anum Sadruddin; Shahryar Noordin (Journal of the Pakistan Medical Association, 2026)
Objective: To evaluate the 30-day morbidity and mortality after hip surgery in a low-resource setting, and to identify the key risk factors. Method: The retrospective study was conducted in January 2023 at the Department of Orthopaedic Surgery, Aga Khan University Hospital, Karachi, and comprised data of patients having undergone elective and emergency hip surgeries from January 1, 2015, to December 31, 2019. Data regarding demographics, comorbidities, surgical details and postoperative outcomes was noted to identify patient and surgery-related risk factors. Data was analysed using STATA 17. Results: Of 1,221 patients with median age 67 years (interquartile range: 54-76 years), 759(62.2%) were male, and 23(1.9%) died within 30 days. Mortality cases were significantly older (p=0.018) and had a higher burden of comorbidities (p<0.001) than the rest. Dynamic hip screw fixation was the most common procedure 447(36.6%). Mortality was significantly higher for patients requiring intensive care (p=0.003). Increased Charlson Comorbidity Index score, length of hospital stay, failed dynamic hip screw, re-intubation, septic shock and cardiac arrest were independent predictors of 30-day mortality (p<0.05). Conclusion: Advanced age and higher Charlson Comorbidity Index scores were significant associated with 30-dat mortality following hip surgery. Key Words: Hip surgery, 30-day mortality, Comorbidities, Postoperative complications, LMIC.